(untitled) (Journal of Applied Oral Science, 2017)
Acute periradicular abscess is a condition characterized by the formation and propagation of pus in the periapical tissues and generally associated with debilitating pain. Objective: The aim of this study was to compare the overall analgesic effectiveness of two combinations of opioid and non-opioid analgesics for acute periradicular abscess. Material and Methods: This study included 26 patients who sought emergency care in a Brazilian dental school. The patients were randomly divided into two groups: Co/Ac - oral prescription of codeine (30 mg) plus acetaminophen (500 mg), every 4 h, for 3 days or Tr/Ac - oral prescription of tramadol hydrochloride (37.5 mg) plus acetaminophen (500 mg) on the same schedule. Two factors were evaluated: (1) pain scores recorded by the patients in a pain diary 6, 12, 24, 48, and 72 h after treatment, using the Visual Analogue Scale; and (2) the occurrence of adverse effects. Results: In both groups, there was a reduction in pain scores over time. For the Co/Ac group, there was a significant reduction in the scores 12, 24, 48, and 72 hours after treatment (P